Potentiometric and spectrophotometric studies of the mixed-ligand complexes of quercetin and digallic acid with iron(II) and magnesium(II) - (:unkn) unknown (Freund Publishing House Ltd, 2006)
Flavonoids are phenolic compounds widely distributed in plants. The tannin under consideration is produced from nutgalls and distinguish it from other tannins, is known as gallotannic or digallic acid. The potentiometric titration technique has been used to determine the stability constants for the various complexes of iron(II), magnesium(II) with quercetin and digallic acid. Its stability constants were determined potentiometrically by using Calvin-Bjerrum and Irwing-Rossotti methods and by spectrophotometric way. The protonation constants was found for digallic acid logK=8,51. The formation conditions of the mixed complexes consisting of iron(II), magnesium (II) were determined; for quercetin-digallic acid-Fe(II) complex logK=7,65 and for quercetin-digallic acid-Mg(II) complex logK1=6,02 and logK2=3,10 were found.
Keywords: Digallic acid; Naturel dyes; Potentiometri; Quercetin; Spectrophotometri; Stability constants